Os negros em Jacobina (Bahia) no século XIX - Vieira Filho, Raphael Rodrigues (2006)
This study aims the black populations of the region of Jacobina, Bahia, in the 19TH century. There is a bibliography, widely spread in the countryside of Bahia, which states the nonexistence of blacks men in the countryside. These authors are based on the principles of incompatibility between cattle breeding and slavery and also on the strong indigenous presence, which mixed with the white settlers. Based on several documents collection, such as: Correspondences sent to the President of Province by Judges and City Congress, Speeches of the Presidents of the Provinces, digitalized documents by Resgate Project, Books of Registration containing Registrations of Purchases, Sales and Donations, Procurations and the recordings of Letters of Freedom, Crime and Civl Lawsuits, besides the documents published at the end of the 19TH century and beginning of the 20TH century in the Annals of National Library and Historic Documents of the National Library and authors of the 19TH century and beginning of the 20TH century. Were raised data about the black populations and their insertion in the region, contrary to the bibliography mentioned above. Features of the general population composition of the region of Jacobina were studied, based on information taken from the census of the population in the 18TH and 19TH century. The specific regional configuration of the slave population, such as: sex, color/ethnicity, age, using as source the Registrations of Purchases, Sales and Donations and Procurations. The ways freedom was conquered were expressed in the recordings of Letters of Freedom of Jacobina and Morro do Chapéu, consulted. These documents brought besides prices, sex, age, color/ethnicity, the ways of these types of conquers, and other features involved beyond the monetary value of these transactions. In the Crime and Civil Lawsuits it was possible to verify how the conquers of a little more autonomy were traded and expressed in moments and diverse situations